Revisión de las herramientas de gestión pública como plan estratégico que puedan emplearse para mejorar las contrataciones del estado 2023 - Achong Vargas, Luciana (2024)
The present investigation entitled: Review of public management tools as a strategic plan that can be used to improve state procurements, 2023, had the general objective of determining whether public management as a strategic planning tool improves public procurement. The type of research was basic, with a non-experimental design and a search for works indexed to Dialnet, Redalyc, Scopus and SciELO was carried out. The recovery included scientific articles and other sources such as books and degree theses with keywords such as: Public procurement; effectiveness; Public Management; strategic planning and public purchases. As part of its results, it has been found that the Annual Procurement Plan - PAC, is a public management document that allows planning, executing and evaluating the procurement of goods and services that will be convened by the entity during the current year. The PAC is articulated with the Institutional Budget of the entity, among others, so the inclusion of all contracts strictly obeys the satisfaction of the needs of the Entity. In relation to the political guidelines, the rules guide the taxpayer, to guide a deep reform of the State contracting system, based on the experience of international market strategies, in order to consolidate an efficient contracting system and promoter of development. The purpose of operational control is to identify those operations and activities on which it is necessary to apply control measures within contracting activities, as a consequence of their influence on the identified risks, and thus plan such activities so that they are carried out under specified conditions. In conclusion, the PAC, the institutional political guidelines and the operational control are tools that must be used as part of the strategic plan of the institutions to improve state contracting.